Sisters Across the Gulf: Transnational Connections and Frictions in Estonian–Finnish Lesbian Networks of the early 1990s - Põldsam, Rebeka; Taavetti, Riikka (Sweden, 2025)
This article explores the connections between Estonian and Finnish lesbian communities in the early 1990s, based on oral history interviews along with media and archival sources. The Estonian lesbian community formed very quickly in the spring and summer of 1990 and from the very start developed a strong bond with the Finnish lesbian community that then lasted for several years. We have interviewed both Finnish and Estonian lesbian women about the period to learn about the activities of this transnational network and the meaning it carried for its members. In our analysis, we focus on personal and social challenges and tensions, national differences and diverse identities and ways of living as a lesbian woman, but also on the fun and rewarding connections. Our study portrays the transnational network as an example of a relatively equal community, despite the stark economic differences, and addresses how the translocal connections formed as a natural, important and integral part of the development of both these communities.